A Criterion-based Approach for the Systematic and Transparent Extrapolation of Clinical Trial Survival Data - Gabriel Tremblay; Patrick Haines; Andrew Briggs (Journal of Health Economics and Outcomes Research)
**Background:** Trial data often does not cover a sufficiently long period of time to truly capture time-toevent endpoints, however, Health Technology Assessment (HTA) bodies often require overall survival (OS) and progression-free survival (PFS) estimates. Often, significant survival effects are found beyond the time period observed in clinical trials, thus, extrapolation of trial results is required for health economic and HTA evaluations.